LAFAL AL-SABR IN THE QURAN: (THEMATIC STUDY OF MAKKIYAH VERSES) - Saude; Ahmad Arief; Muhammad Sadik Sabry; Muhammad Idzhar (An-Nahdlah: Journal of Islamic Studies, 2023)
The word al-sabr in the Qur'an often appears in various verses, this shows how important the meaning of the word al-sabr is. The Al-Quran has taught the early generations of Muslims the essence of patience and realization in every life problem faced by the Companions of the Prophet. This study tries to examine the pronunciation of the word al-sabr. This research uses a qualitative approach through the thematic analysis of verses. The object of this study focuses on makkiyyah verses in the Qur'an. The results of this study indicate that the narration of the patient verses in the Mecca period can at least be described in three main points, namely the first relates to the mental and physical strengthening of the Prophet Muhammad, second the introduction of the essence of patience in verses that couple the pronunciation of "sabrun" with "jamilun". for the essential type of patience that is clean from all that defiles, the third is the story of the patience of people who lie to the religion of Allah when they have been given punishment, is patience which is of no use at all. This research shows the important value of the contents of the Qur'an, especially in terms of the social dimension which also has a historical background to correlate with the current conditions of society.